2018
DOI: 10.1007/s13197-018-3416-3
|View full text |Cite
|
Sign up to set email alerts
|

Process kinetics on physico-chemical and peroxidase activity for different blanching methods of sweet corn

Abstract: Blanching was performed to inactivate the enzyme using microwave, steam and hot water blanching methods and effect on the enzymatic activity, chemical properties and physical properties of the sweet corn were studied. The effectiveness of each blanching process was evaluated by measuring the loss of peroxidase activity, which was lost after 60, 90 and 120 s with k-values 0.016, 0.024 and 0.028 s-1 following first order kinetics for microwave, steam and hot water blanching respectively. The total sugar, ascorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
8
27
0
Order By: Relevance
“…Similar occurrences were observed in the research of other authors [19,20]. Kachhadiva et al [18] reported, on the other hand, that in the case of some products, a significant decrease of moisture occurs only after a long-lasting blanching process, whereas making blanching time longer influences an increase of moisture.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar occurrences were observed in the research of other authors [19,20]. Kachhadiva et al [18] reported, on the other hand, that in the case of some products, a significant decrease of moisture occurs only after a long-lasting blanching process, whereas making blanching time longer influences an increase of moisture.…”
Section: Resultssupporting
confidence: 88%
“…Tukey's multiple comparison tests showed, on the other hand, that mean values of moisture were significantly differentiated statistically only between the control (0) and 6 min blanching time and control (0) and 8 min blanching time. Kachhadiya et al [18] observed similar relationships while blanching sweet corn kernels. Moisture content significantly increased from 76% to 80.2% in hot water blanching.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, the combination of blanching and sterilization may contribute to the darkness color of kernels. Similar results were obtained by Liato et al (2016) and Kachhadiya et al(2018), where L* values decreased significantly after blanching and sterilization of sweet corn kernels. Treatment E had statistically the smallest total color change (Delta E* parameter) followed by treatment C while treatment D showed the largest total color change.…”
Section: Effect On Colorsupporting
confidence: 86%